Flexor tendon repairs in children: Outcomes from a specialist tertiary centre. Issue 5 (May 2015) - Cooper, L.; Khor, W.; Burr, N.; Sivakumar, B.
Summary We evaluate the functional outcomes of early active mobilization (EAM) after paediatric flexor tendon repair at one centre from 2006 to 2013. A generic rehabilitation protocol was used for the first four to six weeks: boxing glove immobilization (<5 years), dorsal blocking splint and cage (5–10 years) or dorsal blocking splint ± cage (10–16 years). Outcomes were assessed using the Total Active Mobilization (TAM) method of the American Society for Surgery of the Hand and original Strickland criteria (OSC). Sixty-three fingers and 99 tendons were identified, in 57 children. Thirty-five per cent (n = 20) were in zone 2, 23% in zone 1, 18% in zone 5, 14% in zone 3 and 2% in zone 4. Good/excellent results were obtained in 82% by the TAM method and 79% by the OSC of those suitable for analysis (56 tendons in 44 children). The surgical approaches used varied in technique and material; a modified Kessler stitch (n = 42) using prolene (n = 60) represented the majority of core sutures. Epitendinous repair was employed in 76% of repairs (n = 75). The median length of hand therapy follow-up was 83.5 days (IQR 43.5–143.75 days). Complications included: one rupture, one post-operative infection requiring washout and three contractures, two requiring re-operation. EAM is a practical and safe way to rehabilitate children after flexor tendon repair, without increasing ruptures or adhesions. Most children under five are managed effectively in a bulky bandage.